EFEKTIVITAS BIOKONVERSI ECENG GONDOK DAN LIMBAH BUAH TERFERMENTASI SEBAGAI MEDIA TUMBUH LARVA Hermetia illucens - FADHLIL R.C.; WAHYUNI .; BADRIYAH N. (Majalah Ilmiah Peternakan, 2022)
Black soldier fly (BSF) larvae have cellulosic activity in the presence of bacteria in their intestines, organic waste recycling activities using the bioconversion method, bioconversion as a change of organic waste into biomass thro- ugh a fermentation process involving living organisms. Generally, the organisms that play a role in this bioconver- sion process are bacteria, and Hermetia illucens larvae as bioconversion agents of fermented water hyacinth are combined with fruit waste and used as a growing medium. Hermetia illucens larvae with feeding treatment P0 = 100% fruit waste, P1 = fruit waste 25 % + 75% fermented water hyacinth, P2 = 50% fruit waste + 50% fermented water hyacinth, P3 = 75% fruit waste + 25% fermented water hyacinth, larvae used are 6 days old, for all treatmen- ts using 50g Larval mass weight. The results showed that. P3 = 75% fruit waste + 25% fermented water hyacinth produces the highest average weight of the final mass of larvae, namely 124.62 (gr), average feed consumption of 72.72%, average ECD and WRI values of 10.98% and 10.38%. The mixing level of water hyacinth and fermented fruit waste in treatment 3 showed an effective result as a growing medium for Hermetia illucens larvae.